(untitled) (Docentes 2.0 Journal, 2026)
The adoption of digital technologies in education has transformed the educational landscape, making digital skills essential for the learning development of secondary school students. This study aimed to determine the relationship between digital competencies and autonomous learning in secondary school students at an educational institution in the city of Iquitos. It is framed within the positivist paradigm, employing the hypothetico-deductive method, a quantitative approach, and a non-experimental, descriptive-correlational, cross-sectional design. The sample consisted of 54 students from the educational institution, and two questionnaires were administered to assess digital competencies and autonomous learning, with reliability coefficients of 0.882 and 0.834, respectively. Spearman’s rho test was used to analyze the association between the variables. The results indicated a correlation coefficient of Rho = 0.896; statistically significant associations were found between digital competencies and autonomous learning in secondary school students, with magnitudes suggesting a positive relationship between the two constructs. Given the correlational, cross-sectional design, the findings were interpreted as relationships rather than causal effects, highlighting the need to strengthen pedagogical strategies and institutional conditions that enhance these competencies in the school context.